N. gonorrhoeae: pathogenicity of colonial type 5. Issue 5 (May 1978) - Hafiz, S; Jennings, R; McEntegart, M G; Jephcott, A E
Abstract : This paper records the results of the intravenous inoculation of chick embryos with type 5 gonococci and establishes that these strains are pathogenic.